Ethnomathematics on Ayunan Jantra in Bali: Integration of Mathematical Concepts in Culture - Al-Jabar, Sheilla Zalzabilla; Fauzi, Fikri; Hidayat, Wahyu; Fitriani, Nelly; Supriatna, Tatang (IKIP Siliwangi, 2025)
This research explores the concept of ethnomathematics in the ayunan jantra culture in Majalangu Village, Denpasar, Bali. Using an ethnographic approach, this research identifies the mathematical elements contained in the making, structure and use of the jantJra swing. The research was conducted through observation, interviews and documentation when the ayunan jantra was used at a Balinese traditional ceremony. The interview was conducted with Mr. I Made Semara Putra, the manager of the Subak TeBA Majalangu Educational Tourism foundation, Denpasar, Bali. Swing jantra has a philosophy about the values of life, namely the rotation of destiny that we do not know, but must be ready to live it. The main findings of this research are the application of the concepts of geometry, proportion and oscillation in the making and operation of the ayunan jantra. From the geometry aspect, the swing structure includes the position of the support, rotating shaft, and arms that refer to the principles of symmetry and balance. In addition, the measurement of the dimensions of the arms and stand shows the application of the concepts of proportion and comparison. The use of the ayunan jantra also involves the concept of oscillation where the rotating movement resembles harmonic oscillation. This research reveals that Balinese people have intuitively integrated mathematical concepts into their cultural traditions. The findings from this study offer new insights into the relationship between cultural traditions and mathematics learning that could contribute to developing ethnomathematics-based learning in schools. This research is expected to enrich culture-based mathematics learning methods and preserve the local wisdom of the Balinese people.